Mobility for a Better Life: A Fragmented Story of the Migrant - Salimova, Leila (Indonesian Social Work Consortium (ISWC), 2023)
Almost all nations in the world are affected by the migration phenomena, which is becoming more and more widespread and complex. Although they are frequently connected to the concept of globalization in general, the broad social, economic, and political grounds of this movement are varied and not always necessarily known. This paper introduces qualitative research findings from the semi-structured interview with the migrant, who made up her mind to change her life by moving from her home country to Poland in 2020 during the COVID-19 pandemic. The paper utilized such concepts as migration, student mobility, culture shock, the COVID-19 crisis, and social service provision to analyze the findings of the interview. The results from the interview demonstrate the fragmented story full of challenges that the migrant experienced including cultural adaptation, economic constraints, and social support. Despite challenges, the interview participant was able to look at her life opportunistically and gladly shared her story filled with kind people and lessons learned. On the example of one story, this qualitative research helps to reveal some gaps in the social support and migration systems to be improved as well as foresee some issues with migration restrictions in the future.